Computer-assisted CT navigation of posterior pelvic segment osteosynthesis - a case report - Madeja, Roman; Měrka, Ondřej; Bialy, Ľubor; Stránský, Jan; Voves, Jiří; Pometlová, Jana (Úrazová chirurgie, 2020)
INTRODUCTION: Osteosynthesis of posterior pelvic segment injuries with iliosacral screws is one of the most commonly used methods today. The most accurate method of checking these types of operations is the CT navigation. The aim of this study was to evaluate the use of computer-assisted CT navigation during osteosynthesis of posterior pelvic segment in a case report. METHODS AND RESULTS: A 58-year-old patient with pelvic injury underwent osteosynthesis of the left sacroiliac joint disjunction using a cannulated screw. This operation was performed under the control of computer- assisted CT navigation. The time of individual parts of the surgery as well as the dose of perioperative X-ray irradiation were monitored. DISCUSSION: Currently, computer-assisted CT navigation is not commonly used in pelvic trauma; there is more experience with CT-guided pelvic surgery. In the world literature, there are papers on smaller cohorts of patients where its benefit over standard methods is demonstrated. CONCLUSION: The use of computer-assisted CT navigation in posterior pelvic segment osteosynthesis allows better orientation in the sacroiliac region. Precise targeting of screws to the sacrum in segments S1, S2 is possible.
Keywords: polytrauma; kostní šrouby; Multiple Trauma; Pelvis; Surgery, Computer-Assisted; vnitřní fixace fraktury; lidé středního věku; lidé; mužské pohlaví; PET/CT; Male; chirurgie s pomocí počítače; Positron Emission Tomography Computed Tomography; Middle Aged; Fracture Fixation, Internal; Bone Screws; pánev; Humans